Personalization of CM Injection Protocols in Coronary Computed Tomographic Angiography (People CT Trial). (17th January 2020) - Eijsvoogel, N. G.; Hendriks, B. M. F.; Nelemans, P.; Mihl, C.; Willigers, J.; Martens, B.; Wildberger, J. E.; Das, M.
Abstract : Aim . To evaluate the performance of three contrast media (CM) injection protocols for cardiac computed tomography angiography (CCTA) based on body weight (BW), lean BW (LBW), and cardiac output (CO). Materials and methods . A total of 327 consecutive patients referred for CCTA were randomized into one of the three CM injection protocols, where CM injection was based on either BW (112 patients), LBW (108 patients), or CO (107 patients). LBW and CO were calculated via formulas. All scans were ECG-gated and performed on a third-generation dual-source CT with 70–120 kV (automated tube voltage selection) and 100 kVqual.ref /330 mAsqual.ref . CM injection protocols were also adapted to scan time and tube voltage. The primary outcome was the proportion of patients with optimal intravascular attenuation (325–500 HU). Secondary outcomes were mean and standard deviation of intravascular attenuation values (HU), contrast-to-noise ratio (CNR), and subjective image quality with a 4-point Likert scale (1 = poor/2 = sufficient/3 = good/4 = excellent). The t -test for independent samples was used for pairwise comparisons between groups, and a chi-square test ( χ 2) was used to compare categorical variables between groups. All p values were 2-sided, and a p < 0.05 was considered statistically significant. Results . Mean overall HU and CNR were 423 ± 60HU/14 ± 3 (BW), 404 ± 62HU/14 ± 3 (LBW), and 413 ± 63HU/14 ± 3 (CO) with a significant difference between groups BW and LBW (p = 0.024 ). The proportion of patients with optimal intravascular attenuation (325–500 HU) was 83.9%, 84.3%, and 86.9% for groups BW, LBW, and CO, respectively, and between-group differences were small and nonsignificant. Mean CNR was diagnostic (≥10) in all groups. The proportion of scans with good-excellent image quality was 94.6%, 86.1%, and 90.7% in the BW, LBW, and CO groups, respectively. The difference between proportions was significant between the BW and LBW groups. Conclusion . Personalization of CM injection protocols based on BW, LBW, and CO, and scan time and tube voltage in CCTA resulted in low variation between patients in terms of intravascular attenuation and a high proportion of scans with an optimal intravascular attenuation. The results suggest that personalized CM injection protocols based on LBW or CO have no additional benefit when compared with CM injection protocols based on BW.